PENERAPAN PEMBELAJARAN BERBASIS PENGALAMAN DI LPTK BAGI PENYIAPAN GURU PROFESIONAL - Ghufron, Anik (MAJALAH ILMIAH PEMBELAJARAN, 2007)
According to "Undang-undang nomor 14 tahun 2005 tentang Guru dan Dosen ", teacher college institution (LPTK) has a strategic role in preparing professional teachers with four competencies: pedagogical, personal, professional, and social competencies. In this context, LPTK is requested as a good educational institution to prepare professional teachers. To anticipate that challenge, LPTK needs to do some programs to prepare professional teachers. One of them is to apply experience-based instruction because the instruction is the realization of the curriculum design in the classroom. Some activities to support the application of experience-based instruction are the synchronization of competency formulation, development of the competency-based field study program, and development of the performance-based evaluation.